2021
DOI: 10.21203/rs.3.rs-558352/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diacylglyceryl-N,N,N-trimethylhomoserine-dependent Lipid Remodeling in a Green Alga, Chlorella Kessleri

Abstract: Membrane lipid remodeling contributes to environmental 19 acclimation of plants. In a green lineage, a betaine lipid, diacylglyceryl-N,N,N-trimethylhomoserine (DGTS), is included exclusively among green algae and non-flowering plants. Here we show that, a green alga, Chlorella kessleri, reported to exceptionally possess no DGTS, synthesizes it specifically under phosphorus-deficiency conditions through the eukaryotic pathway via the ER. Simultaneously, phosphatidylcholine and phosphatidylethanolamine, which ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In line, Tanaka et al (2020) excluded the responsibility of slr2103, a homolog of DGAT2 in Synechocystis, for TG synthesis whereas Aizouq et al (2020) reported that slr2103, which was found as a homolog of the phytyl ester synthase 2 (PES2) gene of Arabidopsis thaliana (Lippold et al, 2012), was responsible for the synthesis of both phytyl ester and TG. Independently of the above research on Synechocystis, we have long been aware of a neutral lipid in Synechocystis with similar TLC-mobility to that of TG during our research focused on algal TG synthesis (Shiratake et al, 2013;Sato et al, 2014;Hirai et al, 2016;Hayashi et al, 2017;Otaki et al, 2019;Oishi et al, 2022), and have investigated the chemical structure of the TG-like lipid and the function of slr2103 in Synechocystis.…”
Section: Introductionmentioning
confidence: 99%
“…In line, Tanaka et al (2020) excluded the responsibility of slr2103, a homolog of DGAT2 in Synechocystis, for TG synthesis whereas Aizouq et al (2020) reported that slr2103, which was found as a homolog of the phytyl ester synthase 2 (PES2) gene of Arabidopsis thaliana (Lippold et al, 2012), was responsible for the synthesis of both phytyl ester and TG. Independently of the above research on Synechocystis, we have long been aware of a neutral lipid in Synechocystis with similar TLC-mobility to that of TG during our research focused on algal TG synthesis (Shiratake et al, 2013;Sato et al, 2014;Hirai et al, 2016;Hayashi et al, 2017;Otaki et al, 2019;Oishi et al, 2022), and have investigated the chemical structure of the TG-like lipid and the function of slr2103 in Synechocystis.…”
Section: Introductionmentioning
confidence: 99%
“…Even some algae contain only betaine lipids and no PC such as Chlamydomonas reinhardtii whereas some other do not contain betaine lipids but only PC such as Chlorella sorokiniana [53, 54]. Nonetheless, it was found very recently that in phosphate starvation Chlorella kessleri replaced PC by DGTS completely although it was previously thought to be an alga that produces no betaine lipid [55]. Therefore, we could suppose that the inability of freshwater organisms to make PC and DGTS “compatible” through fatty acid chain adjustments forces these organisms to avoid PC/DGTS mixed bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the fatty acid composition of DGTS was nearly identical to that of PC and PE in phosphorus-replete conditions (Oishi et al, 2022). C. kessleri was found to contain a homolog of the C. reinhardtii BTA1 gene, and the expression of this gene appears to be induced under phosphorus-deprived conditions in order to lower the alga's phosphorus demand (Oishi et al, 2022). Similar findings were reported in the heterokont Nannochloropsis oceanica, which contains both DGTS and PC under nutrient replete growth conditions.…”
Section: Betaine Lipids May Replace Pc As a Fatty Acid Editing Hub In...mentioning
confidence: 95%
“…Under optimal growth conditions, the green alga Chlorella kessleri does not contain DGTS, and contains PC as the dominant extraplastidic lipid. Within 48 hours of transfer to phosphorus-deficient conditions, this alga almost completely replaces the phospholipids PC and phosphatidylethanolamine (PE) with an equivalent amount of DGTS (Oishi et al, 2022). Interestingly, the fatty acid composition of DGTS was nearly identical to that of PC and PE in phosphorus-replete conditions (Oishi et al, 2022).…”
Section: Betaine Lipids May Replace Pc As a Fatty Acid Editing Hub In...mentioning
confidence: 99%
See 1 more Smart Citation